2021
DOI: 10.3390/v13122442
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Deltacoronavirus Utilizes Sialic Acid as an Attachment Receptor and Trypsin Can Influence the Binding Activity

Abstract: Porcine deltacoronavirus (PDCoV) is a novel coronavirus that causes diarrhea in nursing piglets. Studies showed that PDCoV uses porcine aminopeptidase N (pAPN) as an entry receptor, but the infection of pAPN-knockout cells or pigs with PDCoV revealed that pAPN might be not a critical functional receptor, implying there exists an unidentified receptor involved in PDCoV infection. Herein, we report that sialic acid (SA) can act as an attachment receptor for PDCoV invasion and facilitate its infection. We first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Trypsin has been demonstrated to increase viral infectivity in cells ( 36 ). In a similar vein, after 24 h of incubation on ST cells without trypsin, no cells were infected with PDCoV by immunofluorescence, and when 4 μg/mL of trypsin was added, virus replication increased 70.4 times that of the non-addition group, which could be because trypsin promotes PDCoV attachment to cells ( 37 ) cleaving and activating the PDCoV S protein, allowing the virus to enter cells ( 38 ). Trypsin has also been proposed to promote viral replication by provoking the fusion of infected cells’ intercellular membranes ( 39 ).…”
Section: Discussionmentioning
confidence: 85%
“…Trypsin has been demonstrated to increase viral infectivity in cells ( 36 ). In a similar vein, after 24 h of incubation on ST cells without trypsin, no cells were infected with PDCoV by immunofluorescence, and when 4 μg/mL of trypsin was added, virus replication increased 70.4 times that of the non-addition group, which could be because trypsin promotes PDCoV attachment to cells ( 37 ) cleaving and activating the PDCoV S protein, allowing the virus to enter cells ( 38 ). Trypsin has also been proposed to promote viral replication by provoking the fusion of infected cells’ intercellular membranes ( 39 ).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, CD163 and pAPN double-gene-knockout pigs exhibited decreased susceptibility to PDCoV [92]. A recent study reported that sialic acids serve as a binding receptor of PDCoV [93]; however, whether sialic acids are PDCoV receptors or just attachment factors is still unknown. Additionally, lung fibroblast-like cells, derived from the pAPN knockout porcine alveolar macrophage (PAM) cultures, still supported PDCoV replication to high levels [94].…”
Section: Receptor Usagementioning
confidence: 99%
“…SA can promote the adhesion ability of PDCoV, relating to the intestinal tissue tropism of PDCoV. These results suggest that SA may be a cofactor of PDCoV infection [ 71 ].…”
Section: Secov Infection and The Involvement Of Host Factorsmentioning
confidence: 99%
“…As an extracellular protease, trypsin activates the PDCoV S protein to induce intercellular fusion. Trypsin is needed in the culture and passage of SeCoV, which promotes the fusion of virus and cells and increases the yield of virus [ 71 , 77 , 78 , 79 ] ( Figure 3 ).…”
Section: Secov Infection and The Involvement Of Host Factorsmentioning
confidence: 99%